The viability of applying ADR methods for resolving medical malpractice disputes in Indonesia - Susila, Muh Endriyo; Jahn Kassim, Puteri Nemie (2015)
The nature of doctor-patient relationship has significantly changed in Indonesia since the increase of medical malpractice cases. Massive publicity on alleged medical malpractice cases by the media has triggered public awareness towards patient safety issues and created hostile environment within the healthcare setting. Although medical malpractice cases in Indonesia can be tried under civil or criminal proceedings, many injured victims prefer to try their cases under criminal proceedings. The reasons for bringing the cases to criminal courts revolve around the issues of anger, vengeance and promoting deterrence. Further, criminal proceedings have also been opted by medical malpractice lawyers to avoid the difficulty in proving doctor’s negligence if the case is brought into civil court. Nevertheless, bringing malpractice cases to be tried through criminal courts destroys doctor-patient relationship and tarnished the reputation of the doctors abruptly. Doctors are instantly labeled as criminals before they are found guilty by the courts. Thus, resolving medical malpractice through litigation has many negative implications other than being lengthy in nature with unreasonable costs. Undeniably, patient safety could be better protected through more amicable settlements rather than criminal prosecution. Dispute resolution mechanisms should be introduced and promoted in Indonesia as an alternative to the litigation process with hope of providing redress to victims of medical malpractice in a more amicable manner.